Experimental and numerical investigation of turbulent diffusion flames in a laboratory combustor with a slot burner. (1st July 2016) - Branco, J.; Coelho, P.J.; Costa, M.
Highlights: Investigation of turbulent diffusion flames in a combustor with a slot burner. OH ∗ imaging and temperature and gas species concentrations are reported. Regions of highest temperatures coincided with regions with maximum OH ∗ intensity. Addition of CO2 to oxidizer lowered OH ∗ intensity and suppressed NO formation. Model was able to satisfactorily predict the experimental data. Abstract: This work investigates both experimentally and numerically turbulent diffusion flames in a laboratory combustor with a slot burner. Experiments were carried out using a mixture of natural gas (75 vol.%) and hydrogen (25 vol.%) as fuel and three oxidizers with compositions of 35% O2 /65% N2, 35% O2 /32.5% N2 /32.5% CO2 and 35% O2 /20% N2 /45% CO2 . For these three oxidizers, hydroxyl radical chemiluminescence (OH ∗ ) imaging and spatial distributions of temperature and of O2, CO2, CO and NOx concentrations are reported, which enabled to identify the location and structure of the reaction zone. The regions of highest temperatures coincided with the regions where the OH ∗ intensity was maximum. Moreover, the addition of CO2 to the oxidizer forced the reaction to take place further downstream, lowered the OH ∗ intensity and suppressed the NO formation. On the modeling side, numerical simulations were carried out using the ANSYS Fluent 15.0 commercial code. Turbulence was modeled using the k – ε realizable model. The eddy dissipation concept was employed along with a chemical mechanism comprising 42 transported species and 167 chemical reactions. The model was able to satisfactorily predict the temperature and the concentrations of O2 and CO2, but discrepancies were found in the prediction of the CO concentration.